Descriptive analysis of longitudinal endoscopy for exercise‐induced pulmonary haemorrhage in Thoroughbred racehorses training and racing at the Hong Kong Jockey Club – letter. (19th January 2015) - Preston, S.; Riggs, C. M.
Abstract : See article by Preston et al . andcorrespondence by Morley and Hinchcliff Abstract : See article by Preston et al . andcorrespondence by Morley and Hinchcliff